1981
DOI: 10.1073/pnas.78.2.1057
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of K+ efflux in cultured mouse fibroblasts, by mutation or by diuretics, permits growth in K+-deficient medium.

Abstract: The mouse fibroblastic cell line LM(TK-) is unable to grow at external K+ concentrations below a threshold value of 0.4 mM. At subthreshold K+ concentrations, LM(TK-) cells rapidly lose intracellular K+ and eventually lyse. We have analyzed the pathwayprimarily responsible for K+ efflux under these experimental conditions and report its specific inhibition by two diuretics, furosemide and bumetanide. Bumetanide, an analog of furosemide, was a more potent inhibitor (by several orders of magnitude) than was furo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…If the loss of this system were responsible for the ability of LTK-5 to grow at 0.2M K, then inhibiting the system with diuretics should confer a similar ability on the parent strain, LMTK − . We showed that this was indeed the case: thus, the reduction of K efflux either by mutation or by diuretics inhibition permitted growth in K + deficient medium (39). In a later paper, we showed that the diuretic-sensitive system requires both Na + and Cl − , and can be described as a K + Na + Cl − cotransport system (40).…”
Section: Membrane Transport In Mammalian Cellsmentioning
confidence: 89%
“…If the loss of this system were responsible for the ability of LTK-5 to grow at 0.2M K, then inhibiting the system with diuretics should confer a similar ability on the parent strain, LMTK − . We showed that this was indeed the case: thus, the reduction of K efflux either by mutation or by diuretics inhibition permitted growth in K + deficient medium (39). In a later paper, we showed that the diuretic-sensitive system requires both Na + and Cl − , and can be described as a K + Na + Cl − cotransport system (40).…”
Section: Membrane Transport In Mammalian Cellsmentioning
confidence: 89%
“…Although Na/K/Cl cotransport is a bidirectional transport system (10) and the directionality of the net flux in VSMC is not known, preliminary data suggests that this system mediates net efflux under physiological conditions, as has been shown to be true in MDCK cells (22) and L cells (23). On this basis, if it is assumed that the present experimental conditions mimic the physiological state, an increase in activity of Na/K/Cl cotransport could actually lead to a net decrease in intracellular Na.…”
Section: And 5)mentioning
confidence: 91%
“…These peptides contain approximately [20][21][22][23][24][25][26][27][28][29][30] amino acids, and the amino acid sequence and the cDNA sequence have been identified (2). ANF has been shown to cause vasorelaxation as well as diuresis and natriuresis (3).…”
mentioning
confidence: 99%
“…2 " 4 There are no data available to prove this assumption, however, and other functions may be more important, for instance, a K + inward transport driven by the inwardly directed Na + gradient. 23 We have studied the relation between outward transport of Na + and K + and inward transport of K + , using Rb + as a tracer, and have found that the transport rates in the two directions are closely linked to each other ( fig. 11).…”
Section: -22mentioning
confidence: 99%
“…10), indicating that the activity of the cotransport system is either genetically determined 23 or governed by a plasma factor that remains unchanged over long periods of time.…”
mentioning
confidence: 99%